Exploring mood through emotional dimensions: A PANAS-based study and its implications for Islamic counseling programs - Hidayatullah, Muhammad Rahmat; Suryani, Suryani; Syaputra, Yogi Damai (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2024)
Emotional regulation plays a vital role in supporting psychological well-being and academic success, particularly within Islamic educational environments. This study aims to examine the emotional dynamics of students in the Islamic Guidance and Counseling Program and to identify their implications for the development of culturally responsive counseling services. A descriptive quantitative approach was utilized, employing the Positive and Negative Affect Schedule (PANAS) to measure levels of Positive Affect (PA) and Negative Affect (NA) among students selected through purposive sampling over a three week period. The findings revealed that students consistently reported higher positive emotions, such as pride and enthusiasm, compared to negative emotions, such as worry and anger. Female students exhibited greater emotional variability than male students, with a higher tendency to experience both elevated positive affect and fluctuations in negative affect. These results emphasize the necessity of integrating Islamic values such as tawakkal (trust in God), patience, and gratitude into counseling interventions to enhance emotional resilience. The study recommends the adoption of data-driven emotional assessments to develop adaptive, gender-sensitive, and evidence-based counseling programs that foster holistic student development in Islamic educational settings.